Risks and trends of red blood cell transfusion in obstetric patients: a retrospective study of 45, 213 deliveries using administrative data. Issue 9 (22nd June 2017) - Shehata, Nadine; Chassé, Michaël; Colas, Jo Ann; Murphy, Malia; Forster, Alan J.; Malinowski, Ann K.; Ducharme, Robin; Fergusson, Dean A.; Tinmouth, Alan; Wilson, Kumanan
Abstract : BACKGROUND: Transfusion data for obstetric patients are scarce. Identifying characteristics associated with red blood cell transfusion (RBCT) is of importance to better identify patients who would benefit from blood conservation strategies as the risk of alloimmunization from RBCT has the potential to affect the fetus and newborn. STUDY DESIGN AND METHODS: We conducted a retrospective cohort study using hospital administrative data to identify trends and risk factors of RBCT in obstetric patients. Data were analyzed according to the mode of delivery. RESULTS: A total of 45, 213 deliveries were captured between January 1, 2007, and December 31, 2013. A higher proportion of patients undergoing cesarean sections (C/Ss) received an RBCT (2.3%) compared to other modes of delivery (0.7% for spontaneous vaginal delivery, 1.5% for instrumental delivery; p  <  0.001). In addition, the risk of RBCT increased over the 7‐year period for those patients undergoing C/S (relative risk [RR], 1.56; 95% confidence interval [CI], 1.14‐2.15). An unavailable hemoglobin (Hb) level (RR, 12.94; 95% CI, 7.39‐22.66) and Hb level of 70 to 80 g/L (RR, 7.78; 95% CI = 5.21‐11.60) were strongly associated with RBCT among women undergoing C/S. Earlier gestational age at induction increased the risk of RBCT across all modes of delivery. CONCLUSIONS: The higher frequency of RBCT for unknown and low Hb supports the need for predelivery patient blood management at the time of delivery. The additional risk factors associated with RBCT identified may be used to develop risk stratification tools by mode of delivery to assist in the identification of patients at the highest risk of requiring RBCT.